Doping and plasmonic Raman enhancement in hybrid single walled carbon nanotubes films with embedded gold nanoparticles. (July 2021) - Wroblewska, Anna; Gordeev, Georgy; Duzynska, Anna; Reich, Stephanie; Zdrojek, Mariusz
Abstract: Novel optical hybrid materials can be produced with carbon nanotubes and metallic nanoparticles. Such hybrids may allow coupling between plasmons in metals and excitons in nanotubes. We develop novel hybrid materials in the form of thin films using vacuum filtration, where gold nanoparticles are embedded into the entire volume of the nanotube film, not only on the top of the film. After producing semiconducting and metallic hybrids, we investigate their electronic properties. Free charge carriers in metallic nanoparticles extend into nanotubes, resulting in the doping effect. The doping effect manifests in changes the phonon energy and lifetime, scaling with gold nanoparticle concentration. We implement statistical Raman analysis and determine 20 meV p-doping. The statistical data were cross-correlated with parameters of the 2D and G modes, which helped to clearly disentangle doping and strain. Further, we studied optical properties of the films. The gold nanoparticles enhance the CNTs Raman scattering efficiency. The enhancement is wavelength dependent, as confirmed by resonance Raman spectroscopy on radial breathing modes. The enhancement factors vary from 2 to 3.5 times, with maximum at 1.7 eV. The shapes of enhanced resonance Raman profiles were interpreted with the fifth-order perturbation theory incorporating plasmonic effect. Graphical abstract: Image 1